Resources in play: Bricolage in the Toy Store(y) - Baker, Ted (Journal of Business Venturing, 2007)
This paper analyzes the “Toy Store(y)” narrative by imagining the words and perspectives of several participants other than those from whose perspective the original story is told. By applying the lens of bricolage to a series of critical events and activities described in the Toy Store(y), I illustrate the theoretical and practical application of prior research findings on both bricolage and improvisation and extend these to make suggestions for useful future research and teaching in these areas.